Red wine and wine pomace reduced the development of insulin resistance and liver steatosis in HFD-fed mice. (July 2017) - Rosenzweig, Tovit; Skalka, Nir; Rozenberg, Konstantin; Elyasiyan, Uriel; Pinkus, Anna; Green, Benzi; Stanevsky, Maria; Drori, Elyashiv
Highlights: High fat diet-fed mice were used as a model for non-alcoholic fatty liver disease. No hepatic adverse effects were detected following moderate wine consumption. Grape-skin maceration time affect the beneficial properties of the wine. Long-maceration wine improved glucose tolerance and hepatic lipid accumulation. Pomace improved glucose tolerance, insulin sensitivity and reduced hepatic TG. Abstract: Nonalcoholic fatty liver disease is the hepatic manifestation of the metabolic syndrome. While moderate wine consumption eliminates various components of the syndrome, alcohol consumption is not recommended for NAFLD. Aim: To investigate the potential benefits of red wines, containing different polyphenol levels, and pomace on hepatic health and glucose tolerance in high-fat diet (HFD)-fed mice. HFD-fed mice were supplemented with red wine, prepared according to different maceration protocols: short (SM), regular (RM) or long maceration (LM), non-alcoholic wine, equivalent doses of ethanol, or pomace. Maceration time was found to affect the beneficial properties of wine; LM, but not SM or RM-wine, improved glucose tolerance, insulin sensitivity and hepatic steatosis. Pomace, the main waste product of wine industry, improved all parameters measured: body weight gain, glucose tolerance, insulin sensitivity, and hepatic steatosis thus might be used as a supplement with beneficial health outcomes, without the concerns regarding adverse effects of alcohol.